Awareness and Malaria Prevention Practices in a Rural Community in the Ho Municipality, Ghana. (21st May 2019) - Diema Konlan, Kennedy; Amu, Hubert; Konlan, Kennedy Dodam; Japiong, Milipaak
Abstract : Background . Malaria is no doubt a burden on both the financial and human resources of Ghana. In this study, we examined the awareness of malaria prevention practices among indigenes of Godokpe, a rural community in the Ho Municipality of Ghana. Methods . This descriptive cross-sectional survey that used a self-developed questionnaire recruited 246 residents of Godokpe who were aged 18 years and above using a systematic sampling technique. The Statistical Package for Social Sciences (SPSS) was used to analyze data into descriptive and analytical statistics. The descriptive statistics comprised frequency, percentage, and means. Also, analytical statistics of cross tabulation was conducted considering a p<0.05 at a 95% Confidence Interval to be statistically significant. Findings . About 54% and 20% of the respondents, respectively, had satisfactory and good levels of knowledge on malaria prevention. The methods used in malaria prevention included mosquito coils (72%), cleaning and prevention of water stagnation (62%), mosquito spray (54%), and mosquito net (59%). Also, malaria treatment methods mostly used were quinine (70%) and chloroquine (50.4%). The major sources of information on malaria were television (74%), health professionals (66%), schools (62%), family/friends (60%), and the Internet (51%). Conclusion . School children showed good understanding of malaria and its vectors. There is, therefore, the need to increase the empowerment of teachers with appropriate health information including malaria so that they can continue to deliver malaria information to the pupils.